2008
DOI: 10.1542/peds.2007-1641
|View full text |Cite
|
Sign up to set email alerts
|

Early Determinants of Fractures in Rett Syndrome

Abstract: Girls and young women with Rett syndrome are at increased risk of fracture. Those with mutations found previously to be more severe and those with epilepsy have an increased propensity toward fractures. Improved understanding of the risk factors for fracture could contribute to better targeting of interventions to decrease fracture incidence in this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 39 publications
4
86
2
1
Order By: Relevance
“…Vitamin D status) environmental and genetic risk factors. Risk factors for fractures such as genotype 173 and use of certain anti-epileptic medications 181 did not always correlate exactly with those for low bone density, which also varied by outcome parameter and body site. For example, right femoral neck areal bone mineral density was particularly impaired with increasing age and lack of mobility in comparison to other parameters.…”
Section: Bone Healthmentioning
confidence: 87%
See 1 more Smart Citation
“…Vitamin D status) environmental and genetic risk factors. Risk factors for fractures such as genotype 173 and use of certain anti-epileptic medications 181 did not always correlate exactly with those for low bone density, which also varied by outcome parameter and body site. For example, right femoral neck areal bone mineral density was particularly impaired with increasing age and lack of mobility in comparison to other parameters.…”
Section: Bone Healthmentioning
confidence: 87%
“…Susceptibility to osteopenia and fractures was first highlighted through US 171 and Australian research. 172,173 Fracture risk was four times that of the general female population, and specifically increased in those with p.Arg168* and p.Arg270*mutations (see Fig 2). 173 Several Danish, 174,175 US 176,177 and further Australian studies 178,179 have also investigated which particular bone parameters were most adversely affected and their potential nutritional, 180 (e.g.…”
Section: Bone Healthmentioning
confidence: 91%
“…We also found that a diagnosis of epilepsy increases fracture risk, even after adjusting for genotype 4. In the present study, we have investigated the association between fracture risk and commonly used AEDs in the same population base, taking into account duration of use, mobility and MECP2 mutation type.…”
Section: Introductionmentioning
confidence: 92%
“…Reduced bone mineral density (BMD)2 3 and a fracture rate nearly four times that of the general population4 have been reported in this condition with the most commonly fractured bone being the femur. The principal genetic cause of RTT is a spectrum of loss-of-function mutations within the X linked MECP2 gene 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation